Engendering Charismatic Economies: Pentecostalism, Global Political Economy, and the Crisis of Social Reproduction - Barker, Isabelle V. (Conference Papers -- American Political Science Association, 2005)
Pentecostalism is the fastest growing religion in the world today. A number of explanatory theories exist, but in this paper, I hone in on the nexus between economic restructuring and Pentecostalism to explore this extraordinary expansion. Bringing together the work of feminist political economists and of Karl Polanyi, I argue that neo-liberal globalization threatens mechanisms for meeting social reproductive needs. Neo-liberalism cannot meet these needs on its own, and I suggest that Pentecostalism addresses these gaps, effectively embedding neo-liberal economic policies. It does so by facilitating norms and practices on the part of individual adherents to provide for the care work required for human reproduction; to adopt norms required of a neo-liberal labor force; and, to embrace the kind of transnational social identity that is compatible with labor migration and global markets. ..PAT.-Conference Proceeding
Keywords: CHRISTIANITY; GLOBALIZATION; Globalization; PENTECOSTALISM; Pentecostalism; Polanyi, Karl, 1886-1964; RELIGION & sociology; feminism; feminist political economy; neo-liberalism; social reproduction